Perancangan Relayout Warehouse Finish Goods dengan Metode Class Based Storage (CBS) di PT.XYZ Gresik - Habibillah, Muchammad Syauqi; Murnawan, Hery (SURYA TEKNIKA, 2025)
PT. XYZ is a ceramic tile manufacturing company that is facing warehouse challenges due to increased production, such as disorganized storage and high material handling costs. A warehouse layout redesign is required to improve operational cost efficiency. This study aims to propose a more effective warehouse layout using the Class-Based Storage (CBS) method, which classifies products into specific groups. The research was conducted over a period of three months, from December 2024 to February 2025. The results showed that the initial inbound travel distance was 17,877,537.04 meters, while the proposed inbound distance was 17,810,612.67 meters, resulting in a reduction of 66,924.37 meters. For outbound movements, the initial distance was 66,031,993.2 meters, and the proposed distance was 66,015,291.9 meters, achieving a reduction of 1,670.13 meters. The material handling cost per meter was obtained using the formula:(maintenance costs + operator costs) / (inbound material handling moments + outbound material handling moments),which resulted in an initial cost of Rp. 43 per meter, and a proposed cost of Rp. 40 per meter. The initial inbound material handling cost was Rp. 768,734,093, which decreased to Rp. 712,424,507, indicating a cost reduction of Rp. 56,309,586 over three months. For outbound goods, the cost dropped from Rp. 283,937,571 to Rp. 264,061,168, with a total savings of Rp. 19,876,403. The reduction in both distance and material handling costs reflects a significant efficiency improvement, contributing to substantial savings in warehouse operational expenses.